The impact of trade liberalization on the Mexican automobile industry: Evidence from the first 20 years of NAFTA - Gabriela López Noria (Banco de México, 2021)
This paper examines the impact of trade liberalization under NAFTA on the productivity of the Mexican automobile industry. Using a panel of establishments for the period 1994-2014, in a first stage a Cobb-Douglas production function is estimated by the Levinsohn and Petrin's (2003) method (in an alternative exercise by that of Ackerberg, Caves and Frazer, 2015) to obtain a productivity measure. In a second stage, a model is estimated by System GMM to analyze the effect of trade openness on the estimated productivity. The main results indicate that there exists a positive association between trade liberalization and productivity for medium size establishments, but not for small or large establishments. This finding is consistent with that of other authors, who find that trade liberalization results in higher productivity for some firms, but not for all of them (e.g. Lileeva and Trefler, 2010; Bustos, 2011).
Keywords: F13; L62; D24; 330; International Trade Agreements; Liberalization; NAFTA; Tariff; Automobile; Vehicles; Cobb Douglas; Production Function; Productivity